Electronics Module Development Using Heyzine Flipbook on Materials that Change Energy Form - Lutfia Alfina Iskandar; Yuyun Elizabeth Patras; Tustiyana Windiyani (Journal of International Multidisciplinary Research, 2025)
This research aims to create teaching materials on energy conversion for fourth graders at SDN Cilangkap 08 Elementary School in Depok. The development of these materials uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). It started with analyzing the needs, studying the students, designing the product, developing the e-module, getting expert validation, and then testing the e-module on energy transformation. The results from the experts in media, language, and subject matter showed that the e-module using Heyzine flipbooks was valid for use, with an average percentage of 96%. In the testing phase, 32 students provided responses that were highly suitable for use, with an average percentage of 96%. Based on the research results, it can be concluded that the e-module learning material using Heyzine flipbooks on the topic of energy transformation developed in this study is proven to be valid, easy, and engaging for students to use, and highly suitable for study.